Health literacy among rural communities: issues of accessibility to information and media literacy - Haryati Abdul Karim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Health literacy is a very important concept linked to the wellbeing of a nation. A healthy nation is a progressive nation when they can make informed decisions about their health. The concept means one’s cognitive and social ability to gain access, to understand and use health information to make wise decisions to maintain and promote good health on oneself (Nutbeam, 1998). The level of health literacy among rural population in Malaysia is found to be 2.3 percent, lower than urban population according to the 2015 National Health & Morbidity Survey by the Institute for Public Health Malaysia (2015). Hence, a study was undertaken in Sabah to further investigate health literacy rate among rural communities there. Drawing data collected from both survey and semi-structured interviews, rural communities’ health literacy is found to be problematic because it is hampered by problems of accessibility to health information and lack of literacy in searching for health information through the new media. Health information is only accessible through non-media communications like health talks where 70 percent respondents found public health talks to be most useful. On the other hand, findings from semi-structured interviews with 42 informants from four districts in Sabah found that the concept of health literacy as being individually-construct is problematic and needs to be seen from a broader context of socio-economic factor, living conditions of the individuals as well as the quality of health information disseminated in the media.